Strategi Mengatasi Tantangan Belajar Mahasiswa Universitas Pendidikan Indonesia Yang Aktif Dalam Bekerja (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Working students often face various challenges in their studies, such as limited time and fatigue. This study aims to understand the learning strategies of Universitas Pendidikan Indonesia (UPI) students who are actively working in overcoming learning challenges. This study was conducted using a qualitative method through interviews with 20 UPI students who are actively working. The results of the study show that working students face two main challenges: limited time and fatigue. To overcome these challenges, they use various strategies such as time management, prioritizing tasks, and utilizing assistive tools. This study has implications for universities and working students. For universities, it is important to provide support for working students, such as special attention, tuition fee reductions, and time management and learning strategy training. For working students, the strategies presented in this study can help them achieve success in their studies and work.